Spies of the deep: An animal-borne active sonar and bioluminescence tag to characterise mesopelagic prey size and behaviour in distinct oceanographic domains - Chevallay, Mathilde; Jeanniard Du Dot, Tiphaine; Goulet, Pauline; Fonvieille, Nadège; Craig, Cassandra; Picard, Baptiste; Guinet, Christophe (Deep Sea Research Part I: Oceanographic Research Papers, 2024)
International audience Mesopelagic fishes, a central component of marine trophic networks, play a fundamental role in marine ecosystems.However, as they live in highly inaccessible environments, little information is currently available ontheir distribution and abundance. The emergence of biologging technologies has made it possible to use deepdivingpredators as bio-samplers of their environment in under-sampled regions. In this work, we deployed aninnovative miniaturised sonar tag that combines active acoustics with high-resolution GPS, pressure, movementand light sensors on Southern elephant seals, a deep-diving predator feeding on mesopelagic prey. Seals werealso equipped with Conductivity-Temperature-Depth tags. Salinity and temperature depth profiles were used todefine oceanographic domains, allowing us to explore distribution and ecology of mesopelagic prey targeted byseals and the seals’ foraging behaviour. We highlighted strong vertical differences in prey characteristics andbehaviour, with larger, more evasive and less bioluminescent prey in deeper waters. Moreover, prey encounteredin warmer waters were found deeper, were more evasive and displayed a more marked diel vertical migrationbehaviour compared to prey encountered in colder waters, suggesting that prey accessibility and characteristicsdiffer according to oceanographic domains. This study highlights the usefulness of the sonar-bioluminescence tagto infer mesopelagic prey distribution and habitat when deployed on deep-diving predators such as elephantseals.